Sr4Nd2Ti4Nb6O30 tungsten bronze thick films prepared by electrophoretic deposition as a temperature-stable dielectric - Zhu, Xiaoli
Temperature stable dielectrics of tungsten bronze Sr4Nd2Ti4Nb6O30 (SNTN) with maximized dielectric performance are achieved with thick films prepared by electrophoretic deposition. 30 mu m thick SNTN films sintered at 1300 degrees C, exhibit permittivity epsilon > 375, loss tangent tan delta <0.01 and stable to +/- 7.5% of the room temperature value in the temperature range of -95 degrees C to 280 degrees C. This permittivity is similar to 34% higher than that for bulk ceramics (similar to 280) processed under the same conditions. Contrary to the microstructure of ceramics, SNTN thick films exhibit anisotropy of the grain growth with increasing sintering temperature. It is proposed that the observed anisotropy is responsible for the maximization of the dielectric properties and is due to the anisotropic crystal structure of SNTN and to the sintering under constraint. The main contribution of the c axis vibration to the dielectric constant in tungsten bronze SNTN is confirmed. These results are relevant because via tailoring the substrate constraint and sintering conditions the grain anisotropy of SNTN thick films can be controlled and thus the dielectric properties. (C) 2015 Elsevier Ltd. All rights reserved.